In the wake of the compendia : infrastructural contexts and the licensing of empiricism in ancient and medieval Mesopotamia - Johnson, Justin Cale, 1971- (Science, technology, and medicine in ancient cultures ;, 2015)
"In the Wake of the Compendia examines the composition of technical literature in the ancient Semitic-speaking world. Compendia on astrology, magic, medicine, lexicography, and alchemy were composed in several languages and relate to earlier Mesopotamian models. This volume offers new perspectives on the early history of these compendia and their subsequent transmission into later post-cuneiform compilations, curricula, and scholarly writings"--Provided by publisher.